Phacoemulsification of cataract in the case of capsular bag damage - V. U. Rozukulov; T. N. Savranova; A. F. Yusupov (Российский офтальмологический журнал)
Purpose: to analyze the results of complicated cataract phacoemulsification with implantation of various types of intraocular lenses and fixation techniques. Material and methods. 48 patients (51 eyes) with complicated cataracts and weakened ligamentous apparatus of the lens or intraoperative rupture of the posterior lens capsule were divided into two groups: the study group I consisted of 21 patients (23 eyes, aged 71.4 ± 4.5 years) who had cataract phacoemulsification with an implantation of RSP-III IOL which was performed through a 2.4 mm small self-sealing incision using an injector and the control group II consisting of 27 patients (28 eyes, aged 73.6 ± 4.1 years) who had. Cataract phacoemulsification with an anterior chamber IOL implantation using an incision widened to 6.0 mm. Results. By the end of 1-year follow-up period, uncorrected visual acuity was 0.8 ± 0.1 in group 1 and 0.5 ± 0.1 in group II. In 100% of the patients of group 1 the correct position of the IOL was achieved in the early postoperative period (1–3 days) and maintained in the late period (1 year), whereas in group II, two eyes of 28 operated (7.14 %) showed a forward displacement of the anterior chamber IOL, which involved a contact with corneal endothelium. IOP stayed within the normal range in 21 eyes of group I patients (91.3 %), albeit two eyes (8.7 %) revealed transitory hypertension. In group II, 21 eyes (75 %) had normal IOP in the first three postoperative days, while 7 eyes (25 %) revealed an IOP increased to 29–30 mm Hg. In contrast to group I, group II patients showed induced corneal astigmatism which was decreasing during the follow-up period. Conclusion. In the case of a rupture of the posterior capsule during cataract phacoemulsification, or failure of the ligamentous apparatus of the lens of various origins, the implantation of the RSP-III IOL through a small self-sealing incision using an injector is the method of choice, which allows achieving a stable position of the IOL in the early and long-term follow-up periods, and high visual acuity with the minimal values of corneal astigmatism.